BALANCE OF STATE-OWNED ENTERPRISES: Between Public and Private Entities in Providing Protection To The Board of Directors - Firdaus Firdaus; Rahmad Hendra; Samariadi Samariadi; Sonny Zulhuda; Rika Lestari; Hengki Firmanda (Al-Risalah, 2026)
The position of the state-owned Persero has sparked debate, namely as a public body and a private entity. Consequently, the duties and functions of the Persero SOEs, as drivers of the national economy, are not proportionate to the legal risks faced by the board of directors. The accountability of directors is not only subject to private law but also to public law. This research uses a legal normative method, focusing on legal principles and the level of legal synchronisation. This study found that the Company’s SOEs as private legal entities should be managed through private legal mechanisms. Still, the conflict of norms between the concept of state losses and business risks raises fundamental problems. State capital paid to SOEs has become the wealth of SOEs. However, existing regulations still treat it as state wealth, resulting in the legal status of SOEs becoming blurred and in the loss of their independence and personhood. This research contributes to encouraging legal reform of Indonesian SOEs to clarify the position of SOEs as private entities, directors' accountability, and the management of corruption risks by strengthening transparency and applying the doctrine of fiduciary duty and the business judgment rule as benchmarks for management accountability.